The effect of simulating porcelain firing on the elemental composition, microstructure, and mechanical properties of electroformed gold restorations - Youssef S. Al Jabbari; Xanthippi Barmpagadaki; Sara M. Al Taweel; Spiros Zinelis (Elsevier, 2016)
Background/purpose: The mechanical properties of pure gold (Au) are modified by thermal treatments. Thus, the aim of this study was to evaluate the effect of porcelain firing on the elemental composition, microstructure, and mechanical properties of electroformed Au crowns. Materials and methods: Twenty electroformed Au specimens were prepared and divided into two groups. The first group did not receive any treatment (ELEC), and the other group was subjected to porcelain firing (PFIR). After metallographic grinding and polishing, all were investigated by scanning electron microscopy, and elemental composition was determined using energy-dispersive X-ray spectroscopy (EDX). Internal porosity was identified by quantitative image processing. Mechanical properties including Martens hardness (HM), indentation modulus (EIT), elastic index (ηΙΤ), and Vickers hardness (HV) were determined by instrumented indentation testing. The results were statistically analyzed using unpaired t test (α=0.05). Results: A random distribution of tiny pores was identified in cross section, but no significant difference was found between groups [ELEC (%), 0.24±0.13; PFIR (%), 0.31±0.7]. Backscattered electron images revealed no mean atomic number contrast for both groups, indicating that the material was a single-phase alloy, whereas no differences between groups were identified in the composition of C, N, O, and Au after EDX analysis. By contrast, all mechanical properties tested showed statistically significant differences, with the PFIR group showing significantly lower HM, ηΙΤ, and HV but increased EIT compared with those of the ELEC group. Conclusion: Although microstructure and elemental composition of electroformed Au crowns remain unchanged, the mechanical properties are significantly affected by the thermal treatment of porcelain firing.